2016
DOI: 10.5213/inj.1632768.384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combination Treatment of Alpha 1-Adrenergic Receptor Antagonists on Voiding Dysfunction: Study on Target Organs in Overactive Bladder Rats

Abstract: PurposeOveractive bladder (OAB) causes urinary urgency, usually accompanied by frequency and nocturia. Alpha 1-adrenergic receptor (α1-AR) antagonists are known to improve lower urinary tract symptoms associated with OAB. The α1-AR antagonists constitute a variety of drugs according to the receptor subtype affinity. This study investigated the efficacy of tamsulosin, naftopidil, and a combination of the two on OAB rats.MethodsThe OAB rat model was induced by an intraperitoneal injection of cyclophosphamide for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Both α1-AR subtype antagonists alleviate bladder outlet obstruction symptoms, such as residual urine and urinary urge sensation, by reducing the prostate size [ 18 ]. Overactive bladder symptoms, including frequency, urgency, nocturia, and urgency incontinence, were decreased by α1-AR antagonists in clinical and animal studies [ 12 , 19 ]. Furthermore, α1-AR antagonists increase bladder capacity and decrease frequency [ 10 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both α1-AR subtype antagonists alleviate bladder outlet obstruction symptoms, such as residual urine and urinary urge sensation, by reducing the prostate size [ 18 ]. Overactive bladder symptoms, including frequency, urgency, nocturia, and urgency incontinence, were decreased by α1-AR antagonists in clinical and animal studies [ 12 , 19 ]. Furthermore, α1-AR antagonists increase bladder capacity and decrease frequency [ 10 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were sacrificed immediately after evaluating their voiding function by cystometry, following a previously described method [ 10 , 12 ]. The rats were anesthetized using Zoletil 50 (10 mg/kg, interperitoneally; Virbac Laboratories), transcardially perfused with 50mM phosphate-buffered saline (PBS), and fixed with freshly prepared 4% paraformaldehyde in 100 mM phosphate buffer (pH, 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…de Medeiros et al (2003) demonstrated the EA exerted analgesic effect and influenced c-Fos expression in the rats with peripheral neuropathic pain. Increased c-Fos expression represents peripheral nerve activation (Han et al, 2017; Ko et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For immunolabeling of c-Fos in the PVN and vlPAG, c-Fos immunohistochemistry was performed as the previously described method (Han et al, 2017; Ko et al, 2016). Free-floating tissue sections were incubated overnight with rabbit anti-c-Fos antibody (1:1,000; Santa Cruz Biotechnology, Santa Cruz, CA, USA), and the section were then incubated for 1 hr with biotinylated anti-rabbit secondary antibody (1:200; Vector Laboratories, Burlingame, CA, USA).…”
Section: Methodsmentioning
confidence: 99%